Psycho-Spiritual States of Emotions and Their Interventions within Qur’ānic Narratives: Keadaan Emosi Psiko-Spiritual dan Intervensinya dalam Naratif al-Qur'ān - Hassan, Nur Jannah; Ahmad, Nadzrah; El-Muhammady, Asma M. Uthman (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
This article highlights different challenging emotional states exhibited by several prominent figures as narrated in the Qur’ān, and the approach taken by the Qur’ān in presenting and intervening with particular psycho-spiritual processes, which triggered such emotions. Materials and method: Anger (Q.12:84; Q.21:87), sadness (Q.12:86; Q.28:7), hopelessness (Q.19:23), trepidation (Q.19:24), and self-rumination/condemnation (Q.18:6) are among the conditions adversely affecting the emotional states of particular individuals, as exhibited in several Qur’ānic stories. Qualitative in nature, the article employs both content and textual analyses on selective verses of qaṣaṣ (narratives/stories) in the Qur’ān. Content analysis probes deeper into the context of the whole qiṣṣah (story) to examine the underlying causes that triggered certain state of emotion. Whilst textual analysis assists in the clear understanding of the verses in terms of meaning, linguistic value and coherence between verses surrounding the focal issue. Conclusion: The finding suggests that challenging emotions and their interventions as portrayed by Qur’ānic narratives are outcomes of both contextual implications, as well as psycho-spiritual states. These are normal human responses, even by prominent Qur’anic figures. Thoughts, psychological patterns and spiritual awareness pose as major contributing factors towards certain exposition of challenging emotional states. The significance lies in the way that their psycho-spiritual wakefulness has fortified them, enabling them to garner positive coping mechanisms to cope successfully. Abstrak Artikel ini menonjolkan beberapa keadaan emosi mencabar yang dialami oleh sejumlah figura penting seperti yang diriwayatkan di dalam al-Qur’ān, serta pendekatan yang diambil oleh al-Qur’ān dalam membentangkan naratif dan intervensinya terhadap proses-proses psiko-spiritual tertentu, yang mencetuskan emosi sedemikian. Bahan dan kaedah: Marah (Q.12:84; Q.21:87), kesedihan (Q.12:86; Q.28:7), hampa/putus harapan (Q.19:23), kegusaran/gementar (Q.19:24). ), dan kecaman diri (Q.18:6) adalah antara keadaan yang memberi kesan buruk kepada emosi individu tertentu, sepertimana riwayat al-Qur’ān. Bersifat kualitatif, penulisan ini menggunakan kedua-dua analisis kandungan dan tekstual pada ayat-ayat qaṣaṣ (riwayat/kisah) terpilih dalam al-Qur’ān. Analisis kandungan menyelidik jauh ke dalam konteks keseluruhan qiṣṣah (kisah) untuk mengkaji punca asas yang mencetuskan keadaan emosi tertentu. Manakala analisis tekstual membantu dalam pemahaman secara jelas tentang ayat-ayat dari segi makna, nilai linguistik dan koherensi antara ayat-ayat yang mengelilingi isu fokus. Kesimpulan: Dapatan menunjukkan bahawa emosi-emosi yang mencabar dan intervensi mereka, seperti yang digambarkan oleh naratif al-Qur’ān, terbit daripada implikasi kontekstual dan keadaan psiko-spiritual. Hal yang sedemikian adalah tindak-balas normal manusia, walaupun oleh figura-figura penting al-Qur’ān. Pemikiran, corak psikologi dan kepekaan spiritual menjadi faktor penyumbang utama ke arah ekspresi tertentu keadaan emosi yang mencabar. Signifikannya adalah bagaimana ketinggian kepekaan psiko-spiritual berfungsi sebagai pemerkasaan, sehingga mereka memperolehi mekanisme daya tindak positif, lalu mampu berjaya mengatasi apa jua kegetiran rintangan.